A new species and new records of Phlegmacium (Cortinariaceae) from China based on molecular and morphological evidence - Liu, Fei-Fei; Wu, Gang; Yang, Zhu L. (Phytotaxa, 2023)
A new species, Phlegmacium ochraceosquamosum, is described from southwestern China based on morphological and molecular evidence. The new taxon is associated with subtropical fagaceous trees and is characterized by a combination of viscid pale yellow to ochraceous yellow pileus covered with ochraceous brown squamules and fibrils, cylindrical to clavate stipe with ochraceous brown fibrillose girdles, and elongate to subamygdaliform basidiospores. Four species, namely P. glaucopus, P. paracephalixum, P. patrickense, and P. violaceorubens, were first discovered in China. Additional vouchers for two species, namely P. caesiocolor and P. kytoevuorii very recently reported from China, were provided. Illustrated morphological descriptions and comparisons with closely related species are provided. The recognition of these species was further confirmed by phylogenetic analysis based on ITS sequences.